411 Cooperation of occupational health and primary care physicians in germany – insights from a mixed-methods study. (24th April 2018) - Rieger, MA; Michaelis, M; Mosshammer, D; Wilm, S
Abstract : Introduction: Occupational health physicians (OHPs) and primary care physicians (PCPs) have many overlapping fields of work (e.g. general prevention, rehabilitation, return to work process). Yet, studies from several countries have revealed that cooperation between both specialist groups is often scarce. In order to describe barriers and optimisation possibilities, a mixed-method study was performed between 2009 and 2016 in Germany. Methods: First, based on a comprehensive literature review, three focus groups were interviewed (8 OHPs, 7 PCPs, and 8 physicians working in both fields) on their experiences and attitudes towards the cooperation of both professional groups, followed by a qualitative content analysis. 1, 2 In a second step, the categories derived from this qualitative method were operationalised for a standardised survey assessing the physicians´ statements quantitatively. Exploitable questionnaires were returned by 473 OPs (response rate 48%) and 585 PCPs (31%). Based on an exploratory factor analysis (EFA) assessing the structural validity of the questionnaire, mean scores of the dimensions initially described as categories and sub-categories in qualitative data analysis were constructed. Results: The interviews resulted in a broad spectrum of experiences and attitudes including prejudices as well as possibilities for optimisation of cooperation. The analysis of single items of the standardised survey in a subsample allowed for the quantification and pointed out significant but rather small differences between both groups. 3 Within the entire sample, conclusive results could be described by comparative analysis of mean scores derived from the EFA. Generally, despite some critical views, both groups matched with regard to occasions for cooperation. However, the need for cooperation was judged higher by the OHPs than the PCPs. Discussion: Whereas the qualitative study was valuable to gain a broad spectrum of experiences and attitudes, a sound description was available by the quantitative assessment revealing the improvement potential at this important interface. References: . Mosshammer, et al. Z Evid Fortbild Qual Gesundheitswesen 2012. . Mosshammer, et al. Int Arch Occup Environ Health2014. . Mosshammer, et al. Int Arch Occup Environ Health2016.